Nursing pain assessment in non verbal intensive care patient - Villioti, Anastasia; Kalogianni, Antonia; Papageorgiou, Dimitrios; Jahaj, Edison (Health & Research Journal, 2018)
Introduction: It has been found out that pain is one of the most important issues that patients have to deal with while they are hospitalized in an intensive care unit (ICU), especially when they are non-communicative. Nurses play the most important role in the pain assessment through the everyday contact with patients and with the use of a variety of pain assessment tools as well. Aim: The purpose was to determine nurses’ level of knowledge about the use of pain assessment tools (especially pain scales) in the unconscious intensive care patients – To investigate the level of pain assessment tools application in the daily nursing routine by the ICU nurses. Material and Method: A systematic review in the followed database was applied: Pubmed-Medline-Embase. The entry criteria in the review were: a) Publication date: 1990-2017 b) Greek or English language c) the sample of research must necessarily include experienced nurses who work exclusively in an intensive care unit. d) the use of pain assessment tools for non verbal patients should be included in the nursing interventions e) nurses should be responsible for the daily care of non verbal patients f) the results must be concern exclusively non communicative patients. Results: From the research four studies have emerged which met the standards of the review. The common findings among these researches result in the fact that although nurses believe that an effective pain assessment is important to a great extent, very few of them use pain assessment tools according to protocols especially in the unconscious patients. Conclusions: Nursing pain assessment concerning non verbal patients still remain inadequate and doesn’t seem to be a priority during the daily nursing routine. The promotion of education of nurses concerning pain assessment is required and the use of protocols as well in order to ease the process of a reliable and valid pain assessment.